Explorations in Internet Pragmatics : Intentionality, Identity, and Interpersonal Interaction - Lehti, Lotta,; Lexander, Kristin Vold,; Tanskanen, Sanna-Kaisa,; Virtanen, Mikko T.,; Xie, Chaoqun, (Language and Linguistics E-Books Online, Collection 2024., 2024)
This volume takes the reader on an exploration in the dynamics underlying digital interaction. The chapters investigate the ways in which individuals shape and interpret intentions, construct identities, and engage in interpersonal exchanges. Online platforms from forums and Wikipedia to Periscope, YouTube and WhatsApp are approached with multifaceted qualitative methods. Aside from English, languages studied include Bangla, Finnish, French, Hindi, Hungarian, Lithuanian, and Norwegian. The range of phenomena, platforms and languages shed light on the complex and nuanced ways of communication in digital spaces.